A vortex-assisted deep eutectic solvent for parabens extraction in cosmetic samples coupled with high performance liquid chromatography - Nurin Farawani Muhamad Yusri; Noorashikin Md Saleh; Tanusha Devi Elan Solan; Muhammad Zulhaziman Mat Salleh (Penerbit Universiti Kebangsaan Malaysia, 2024)
Parabens, commonly used preservatives in food, cosmetics, and pharmaceutical items, inhibit harmful germ growth. Deep Eutectic Solvents (DES) are intriguing for analyte extraction due to superior properties formed through hydrogen bond acceptors and donor interactions. However, the studies on the optimal DES-based extraction conditions for paraben-containing cosmetics and the accuracy of ‘paraben-free’ labels are limited. The most effective DES (DL-Menthol and decanoic acid, 1:2 molar ratio) was applied to cosmetic samples after heating at 80 °C following optimization parameters. FTIR study confirmed hydrogen bonds in DES samples. Both paraben-containing and paraben-free samples showed methyl, ethyl, and propyl paraben peaks from the HPLC analysis. Cosmetic sample paraben concentrations ranged from 0.53 mg/L to 26.08 mg/L (non-spiked). LOD and LOQ were 0.24 mg/L-1.62 mg/L, 0.73 mg/L, and 4.8 mg/L, respectively. Goals were met by establishing a paraben extraction method using DES and investigating paraben quantities in cosmetics.